Skisme dalam Islam Pendekatan Sosiologis - Evarianisa Endang Trisnani (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
Sociology is a science that describes the state of society complete with structures, layers, and various other interrelated social phenomena. The aim of the Islamic approach in sociology is to understand social phenomena related to worship and muamalat. The importance of the sociological approach in understanding religion can be understood because there are so many religious teachings related to social problems. The research method is qualitative research. The finding is that the amount of religious attention to this social problem encourages religious scholars to understand social sciences as a tool to understand their religion through a sociological approach. The argument is that the relationship between islam and various social problems in the life of community groups and by this means that islam seems to be functionally close to various phenomena in the social life of society.